DESIGN OF AEROSOL GENERATOR SYSTEM BASED ELECTROSPRAY - Sinta Mustika, Widya
Electrospray (ES) is a method of particle formation by utilizing electrostatic forces on surface of solution. This method widely uses, because of inexpensive, controlled particle sized and can be applied in many fields of research. The application of ES as a particle generator have a challenge to reduce the level of particles charge to be carried by gas as aerosol particles. In this thesis, electrospray-based aerosol generators have been constructed utilizing point-to-point configuration. EAG system was optimized by parameters both process (voltage, liquid flow rate) and system configuration (diameter size of orifice, uncovered and full-covered orifice). EAG performance was tested using polystyrene latex (PSL) suspension as liquid inlet and surface-microplasma aerosol charger (SMAC) as a neutralizer. EAG system was applied to generated polymer particles of polyethylene glycol (PEG). The generation of PEG particles was controlled via process parameters (voltage and liquid flow rate). As alternative of SMAC charger, we have constructed a neutralizer based-corona discharge. Bipolar AC charger (BACC) was constructed utilizing ozone generator module (OG). EAG system optimation have presented combination of parameters both system and process, in the condition of SMAC on, i.e 1) size diameter of orifice was 10 mm; 2) liquid flow rate was 1 ?L/menit; 3) spray mode was cone-jet; 4) uncovered orifice configuration. The effects of voltage and liquid flow rate for generation of PEG particle have changed the size distribution particles. BAAC shows the performance of charge level reduction that reached PSL size diameter of 242 nm.